5y - 5 + y + 29 = 6y + 30 - 2y y(5 + 1) + (-5 + 29) = y(6 - 2) + 30 (collect terms) 6y + 24 = 4y + 30 (show collected terms) 2y + 24 = 30 (subtract 4y from both sides) 2y = 6 (subtract 24 from both sides)

**y = 3**(divide both sides by 2)__Check__5y - 5 + y + 29 = 6y + 30 - 2y (your equation) 5*3 - 5 + 3 + 29 = 6*3 + 30 - 2*3 (substitute 3 for y) 15 - 5 + 3 + 29 = 18 + 30 - 6 (perform multiplication) 10 + 3 + 29 = 48 - 6 (add the first pair of terms on each side) 13 + 29 = 42 (add the next pair of terms on each side) 42 = 42 (our answer checks as being correct)